GAMBARAN PENGELOLAAN PERSEDIAAN PERBEKALAN FARMASI DAN BAHAN MEDIS HABIS PAKAI DI APOTEK HALIM MEDIKA BANJARBARU - Amaliyah Wahyuni; Abdul Mahmud Yumassik; Isninoriyah Isninoriyah (Jurnal Insan Farmasi Indonesia, 2023)
Inventory management of pharmaceutical supplies and medical consumables at pharmacies is very important to be considered, because management that is not according to procedures will result in inappropriate use, there will be many expired drugs and budget overlaps. The purpose of this study was to describe the management of pharmaceutical supplies and medical consumables at the Halim Medika Pharmacy Banjarbaru which includes planning, procurement, receipt, storage, expiration checks, control, destruction and withdrawal, recording and reporting. This research was a non-experimental. Data were collected using observation sheets based on the SOP of the Halim Medika Pharmacy and the Minister of Health Regulation No. 73, 2016. The sample in this study were all inventory management of pharmaceutical supplies and medical consumables at the Halim Medika Pharmacy Banjarbaru in February-March 2022. Data analysis was carried out by calculating the percentage of conformity. The results showed that 91% of the activities were appropriate, namely planning, procurement, and receiving activities, 9% were not appropriate, including storage and inspection activities for expiration and based on Permenkes No. 73/2016, 100% activities were in accordance with all, namely control activities, destruction and withdrawal, recording and reporting.